Theological Responses to the Challenges of European Utopian Tradition: Some Teological Programmes of the First Half of the 20th Century - Mikhailov Petr (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
Author supposes that the major social-politic events in European history of the ﬁ rst half of the 20th century have as their root an eschatological utopian tradition that subdues the fact of world Redemption to progressive logic of history. The circle of theologians from Dominican and Jesuit’s Orders associated with Saulchoir (Tournai, Belgium) and Fourvière (Lyon, France) has proposed some theological responses for such kind of opposition to the Christian testimony in the world. They have evident correlation with each other in their general principals and common convictions in the inner structure of theology (cf. M. Blondel and M.-D. Chenu). The theological system has an experience of faith and obedience to the Church as its root, historical research (cf. «théologie de ressourcement», «positive théologie» or historical theology) as its foundation. Two great representatives of Catholic theology — Yves Congar and Henri de Lubac — followed that direction in their scientiﬁc works. Congar succeeded in his project of theology of unity that had to resolve two great schisms: 1) between faith and life, 2) between the Church and the world. He developed his ideas in two vectors of ecclesiology: historical ecclesiology (nature and theology of the Church) and practical ecclesiology (position of the Church in dialogue with the other confessions and external world). Henri de Lubac saw the beginning of the crisis of the world Christianity in the actual condition of contemporary theology as a result of inner opposition between reason and faith. His activity was directed at its overcoming. He ediﬁes the structure of theology from the phenomenon of faith understood as a supernatural gift of God. Further lines were identiﬁed as a unity in social, historical and transcendent dimensions.